A New Commentary on the Old English ‘Prose Solomon and Saturn’ and ‘Adrian and Ritheus’ Dialogues - Wright, Charles D; Hall, Thomas; Hill, Thomas D. (Brepols, 2024)
Who was not born, was buried in his mother’s womb, and was baptized after death? Who first spoke with a dog? Why don’t stones bear fruit? Who first said the word ‘God’? Why is the sea salty? Who built the first monastery? Who was the first doctor? How many species of fish are there? What is the heaviest thing to bear on earth? What creatures are sometimes male and sometimes female? The Old English dialogues <span class=